(untitled) (Bangladesh Journal of Livestock Research, 2020)
This study aimed to identify the genetic variation among different generations of BLRI Cattle Breed-1 (BCB-1) and its relationship with indigenous Pabna cattle. A total of 20 ISAG-FAO recommended microsatellite DNA markers were used for this study. Blood samples were collected randomly from fifteen animals of 1st, 2nd, 3rd and 4th generation of BCB-1, Pabna cattle and RCC as reference cattle breed. The DNA extraction, polymerase chain reaction (PCR) amplification by using microsatellite markers and finally capillary based fragment length analysis was performed by genetic analyzer. The allele number per locus ranged from 5 to 14 in the studied populations. The mean numbers of alleles ranged from 4.95 in 3rd generation of BCB-1 to 7.55 in indigenous Pabna cattle. The mean numbers of alleles per locus decreased in 3rd and 4th generation. Both observed and expected heterozygosity decreased in subsequent generations in BCB-1. The observed heterozygosity decreased in BCB-1 from 2nd to successive generations (0.7257 in 2nd generation to 0.6232 4th generation). The average observed heterozygosity was highest in indigenous Pabna cattle (0.7393). Genetic distance between 3rd and 4th generation of BCB-1 are very low they are more homogenous. Indigenous Pabna cattle and RCC showed more genetic distance from all generations of BCB-1. Dendrogram based on DA genetic distance using unweighted pair group method of arithmetic means (UPGMA) indicated segregation of the four generations of BCB-1 into cluster 1 and 2 which are grouped together and separated from the cluster 3 of indigenous Pabna cattle and cluster 4 RCC population. According to genetic structure of BCB-1, it may treat as a unique cattle population of Bangladesh. Bang. J. Livs. Res. Vol. 26 (1&2), 2019: P. 8-14